How native and exotic Brazilian fruits affect the profile of organic acids and the yeast performance during the mead fermentation process?. Issue 4 (25th March 2022) - da Silva Monteiro Wanderley, Bruna Rafaela; da Silva Haas, Isabel Cristina; Biluca, Fabíola Carina; Brugnerotto, Patricia; de Sena Aquino, Ana Carolina Moura; Oliveira Costa, Ana Carolina; de Mello Castanho Amboni, Renata Dias; Fritzen‐Freire, Carlise Beddin
Abstract: Background: A preliminary investigation was carried out to evaluate the effect of the addition of pulps of feijoa, uvaia, and blackberry on the aliphatic organic acids (AOA) profile and on the yeast activity during the fermentation of meads. Results: A multivariate analysis showed a clear distinction between the samples. The addition of pulps promoted a noticeable increase in malic, lactic, and succinic acids throughout fermentation. Furthermore, these additions resulted in beverages with lower levels of acetic acid. Gluconic acid was predominant in all samples. The mead containing feijoa showed high levels of citric acid. The meads containing blackberry and uvaia reached maximum yeast activity in the first 3 days of fermentation while the control sample and the mead with feijoa showed their highest activity after 7 days. Conclusion: The use of the feijoa, uvaia, and blackberry in mead can represent a good natural source of AOA, thereby improving its fermentative process, besides being an alternative for the valuation of underexploited species of Brazilian fruits.